Bridging romantic and modern eras: structural elements in Byron’s She Walks in Beauty and Auden’s The More Loving One - Darmawan, Rizki; Farani, Yasmin; Putra, Suatmo Pantja (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
This study presents a comparative structural analysis of two renowned poems, “She Walks in Beauty" by G.G. Byron and "The More Loving One" by W.H. Auden, which are widely regarded as some of their finest works. The objective is to identify the similarities and differences between these poems, which originate from distinct poetic eras: Byron’s work represents the Romantic era of the late 18th century, while Auden’s belongs to the Modern era of the early 20th century. To facilitate the comparison, the analysis focuses on three key structural elements of poetry: theme, figures of speech, and imagery. The findings reveal both similarities and differences between the two poems. Shared elements include a focus on love as the central theme, the use of metaphor, personification, and hyperbole in figures of speech, and the incorporation of visual and organic imagery. However, the differences lie in how the theme of love is portrayed. Byron’s poem celebrates the beauty of a woman, while Auden’s reflects the fear of losing a loved one. Additional differences are evident in figures of speech and imagery; Byron employs simile and kinesthetic imagery, which are absent in Auden’s poem. This comparative analysis underscores the influence of distinct poetic eras on these two iconic works’ structural and thematic elements.